Branchial expression of an aquaporin 3 (AQP-3) homologue is downregulated in the European eel (Anguilla anguilla) following seawater acclimation. - Cutler, Christopher Paul; Cramb, Gordon (2002)
A cDNA encoding the homologue of mammalian aquaporin 3 (AQP-3) was isolated by reverse transcription-polymerase chain reaction from the gill of the European eel. The derived amino acid sequence shares 67-70% homology with other vertebrate AQP-3 homologues. Northern blot analysis revealed two AQP-3-specific mRNA species of 2.4 kb and 7 kb. AQP-3 mRNA is expressed predominantly in the eye, oesophagus, intestine (as found in mammals) and the gill; no expression could be demonstrated in the stomach and only low and sporadic levels in the kidney. Quantitative studies demonstrated that, following the 3-week acclimation of freshwater (FW)-adapted yellow and silver eels to seawater (SW), transcript abundance in the gill was reduced by 76% and 97%, respectively. The half time of branchial AQP-3 mRNA downregulation in yellow eels was approximately 10 h, with a maximal 94% decrease in expression after 2 days in SW (compared to time-matched FW controls). However, in fish acclimated to SW for more than 4 days, the fall in AQP-3 mRNA abundance recovered slightly, such that after 3 weeks, expression was 16% of that in time-matched FW controls. The potential roles for this aquaporin isoform in water or solute transport in the eel gill are discussed.